Holograms per i Beni Culturali: le innovazioni per la fruizione artistica - Mazzone, Manuel (Archeomatica, 2024)
Our journey through art and technology continues, unveiling an innovative certainty made in Italy capable of standing out internationally. GeckoWay, an Italian company specializing in software research and development, introduces "VirtualCrab," a mixed reality project. Collaborating with IUAV, GeckoWay merges art and technology to enhance user experience at the National Archaeological Museum in Venice. Exploring "VirtualCrab" and its case study with IUAV, we delve into various holographic representation techniques and devices. Furthermore, we detail a case study involving Gecko-Way and IUAV, showcasing their data processing journey from point clouds to software processing to hologram representation. Looking ahead, we anticipate significant advancements in holographic technology over the next decade, including enhanced accessibility, real-time dynamic displays, improved user interaction, and portability. These developments promise to revolutionize holographic applications across various sectors, ushering in a new era of visual and interactive experiences.